Ritual Makireno Kakaketi (Mandi Kebal) Di Desa Pananaru Kecamatan Tamako Kabupaten Kepulauan Sangihe - Sandiata, Sekri Evan; Masambe, Helen Gratia (Educatio Christi, 2024)
This research not only focuses on the implementation of the Makireno Kakaketi ritual, but also explores the meaning, change, and adaptation of the ritual in the context of modernization and ongoing social change. An ethnographic approach is used to detail the process of implementing the Immune Bathing Ritual. The results highlight the complexity and symbolic richness of the ritual, reflecting the close relationship between spirituality, local wisdom, and the daily lives of the community. In addition, this study also explores the important role of the community in caring for and maintaining the sustainability of the Kebol Bath Ritual as a cultural heritage. The adaptation of the Immune Bathing Ritual to the changing times is also the focus of this research. In the face of modernization and globalization, the people of Pananaru Village uniquely adjust their rituals without losing their traditional essence and values. This research is expected to contribute to the preservation of local cultural heritage and also provide a deeper understanding of how local communities maintain their cultural identity in the face of contemporary challenges.